2008
DOI: 10.1542/peds.2007-2446
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Intake Interferes With the Humoral Immune Response to Recombinant Hepatitis B Vaccine in Patients With Celiac Disease

Abstract: Nonresponse to recombinant hepatitis B surface antigen may be a sign of undiagnosed celiac disease. However, there is a good vaccine response in adequately treated patients. Human leukocyte antigen DQ alleles do not seem to have a primary role. Revaccination is recommended during a controlled gluten-free diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 42 publications
5
80
0
5
Order By: Relevance
“…CD patients may have a failure of induction of humoral immune response, needed for development of long-term immunity, though the relevant mechanism is as yet unclear. Nemes et al (9) observed that the seroconversion rate after HBV vaccination was significantly lower among untreated versus treated and Table 3. Anti-HBs titers according to the groups diet-compliant subjects with CD or control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…CD patients may have a failure of induction of humoral immune response, needed for development of long-term immunity, though the relevant mechanism is as yet unclear. Nemes et al (9) observed that the seroconversion rate after HBV vaccination was significantly lower among untreated versus treated and Table 3. Anti-HBs titers according to the groups diet-compliant subjects with CD or control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…10 Nonresponsiveness to HBV vaccine has been associated with factors such as chronic diseases, smoking, obesity and the male gender. 3 A genetic predisposition to HBV vaccine non-responsiveness has been attributed to particular HLA antigens, 11,12 mainly DQ2 haplotype, which is also involved in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a prospective study, with the same lag time between vaccine and testing, described a failure to respond to HBV vaccine in CD patients on gluten-free diet in a percentage similar to that observed in healthy people. 10 Once again, the hypothesis of immune hyporesponsiveness is not sustainable considering that a high percentage of responders to a booster dose of HBV vaccine is reported in previously vaccinated CD patients without protective anti HBs antibodies. 10 In this case, as well, blood testing was performed in all the patients with the same time interval, a short period after vaccination.…”
mentioning
confidence: 99%
“…Gluten might be implicated because both hepatitis B surface antigen (HBsAg) protein fragments and gliadin peptides bind to HLA-DQ2 molecules and induce proliferation of T lymphocytes. Competition between the proteins may result in defective antibody production (6)(7)(8).…”
mentioning
confidence: 99%